2021
DOI: 10.1109/access.2021.3103893
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Trust in Proactive Conversational Assistants

Abstract: Humans and machines harmoniously collaborating and benefiting from each other is a long lasting dream for researchers in robotics and artificial intelligence. An important feature of efficient and rewarding cooperation is the ability to assume possible problematic situations and act in advance to prevent negative outcomes. This concept of assistance is known under the term proactivity. In this article, we investigate the development and implementation of proactive dialogues for fostering a trustworthy humancom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…So a CUI can be assertive and take the lead when it is appropriate. For example, it has been shown that proactive dialogue strategies have an effect on the human-computer trust relationships depending on context [22] and user-specific information [21]. Furthermore, proactive explanations are able to foster and maintain trust as a response to system breakdowns [38].…”
Section: Position Paper Topicsmentioning
confidence: 99%
“…So a CUI can be assertive and take the lead when it is appropriate. For example, it has been shown that proactive dialogue strategies have an effect on the human-computer trust relationships depending on context [22] and user-specific information [21]. Furthermore, proactive explanations are able to foster and maintain trust as a response to system breakdowns [38].…”
Section: Position Paper Topicsmentioning
confidence: 99%
“…To obtain the emotional tag from our bi-LSTM layer, we concatenated for each embedding of a frame the outputs obtained from the analysis performed in each specific direction (see Equation (1) in which || corresponds to the concatenation operator and L to the size of each LSTM).…”
Section: Feature Extractionmentioning
confidence: 99%
“…By analyzing individuals' behavior, it is also possible to detect a loss of trust or changes in emotions. This capability lets that specific system, such as Conversational Systems and Embodied Conversational Agents (ECAs) [1,2], react to these events and adapt their actions to improve interactions or modify the dialogue contents, tone, or facial expressions to create a better socio-affective user experience [3].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the emotional tag from the Bi-LSTM layers, we concatenated the embeddings of the outputs of each specific direction (see Equation (1) in which || corresponds to the concatenation operator and L to the size of each LSTM).…”
Section: Static Vs Sequential Modelsmentioning
confidence: 99%
“…With the help of an emotion recognizer, other systems could detect loss of trust or changes in emotions by monitoring people's conduct. This capability will help specific systems such as Embodied Conversational Agents (ECAs) [1,2] to react to these events and adapt their decisions to improve conversations by adjusting their tone or facial expressions to create a better socio-affective user experience [3].…”
Section: Introductionmentioning
confidence: 99%